Work reintegration after long-term sick leave: domains of influence on co-workers' ability to be supportive. Issue 19 (10th September 2016) - Petersen, Kirsten Schultz; Labriola, Merete; Nielsen, Claus Vinther; Larsen, Eva Ladekjær
Abstract: Purpose: The purpose of the study is to identify domains of influence on co-workers' ability to be supportive of returning worker during the work reintegration (WR) process. Methods: An ethnographic study design was chosen involving fieldwork at four different workplaces, at an emergency care service, a waste disposal company and at two nursing homes. Qualitative methods for inquiry were used including participant observation, individual- and group interviews of 30 participants. Data were coded and analysed according to a grounded theory approach. Results: Four themes were identified related to domains of influence on co-workers' ability to be supportive of returning worker during the WR process: (1) organisation of work and level of interaction; (2) disruption of work routines, (3) relationship with returning worker and (4) attitudes towards sick leave. Conclusion: The WR process after long-term sick leave is not only influenced by the WR's arrangements made, but also by the co-workers' responses to the process. Work arrangements not only affect the returning worker's ability to return-to-work (RTW) successfully, but also the co-workers' ability to be supportive and their ability to take active part in the process. Implications for Rehabilitation: The process of WR after long-term sick leave involves interaction with co-workers. Domains of influence is in the co-workers' perspective influencing their ability to be supportive during reintegration of a returning worker. Future WR management could benefit from integrating the conditions for co-worker support. We encourage co-workers to be involved in the RTW planning, monitoring and evaluation with particular focus on how the WR arrangements are influencing their work and their ability to be supportive.